LE CONTROLE DES SYSTEMES D’INFORMATION DANS LE SECTEUR PUBLIC : CAS DU MAROC - Farah, Najoua (European Scientific Journal, ESJ, 2014)
The control of information systems (I.S) in the public sector is particularly important, as far as it can promote the master of this technology, contribute to organizational performance and guarantee the keep of the investments spent away from failure. However, any model or approach has not been established yet for those systems to support the appliance of such control and allow the implementation of its objectives. The theoretical study in this research confirms this finding, it was corroborated by an empirical search that was conducted in six I.S in the Moroccan public sector to identify the type and the level of the control applied on those specific system, to elucidate furthermore the relationship between a "good control" and good health "of IS" in the public sector, and to finish, this study was an opportunity to formulate prospects for solving this issue.